PROFITABILITY, CAPITAL STRUCTURE AND ALLOCATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) FUNDS TO CORPORATE VALUES IN BASIC INDUSTRIAL AND CHEMICAL INDUSTRY COMPANIES IN INDONESIA - Yuliana, Indah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Business organizations have the goal of maximizing company value. The era of new developments in management and corporate management shifts efforts to build value based on stakeholder-based strategies, namely to build the value of the company while taking into account and paying attention to stakeholder interests in the framework of achieving company goals. The legitimacy of the company in the eyes of stakeholders can be done with the integrity of the implementation of ethics in doing business and increasing corporate social responsibility. The purpose of this study is (1) to analyze the effect of profitability, capital structure and CSR fund allocation on firm value, (2) to analyze the moderation of Corporate Social Responsibility budget allocation variables to the relationship of profitability and capital structure to firm value. This study uses a quantitative approach using statistical tools and hypothesis testing. The population of this study is 65 basic industrial and chemical sector companies in Indonesia which are listed on the Indonesia Stock Exchange (IDX). The sampling technique was done by purposive sampling, data analysis using multiple linear regression analysis and moderation regression. The results of the study showed (1) Profitability directly had a significant effect on firm value while the capital structure and CSR fund allocation directly did not affect the firm value (2) Allocation of CSR funds strengthened the influence of capital structure on firm value. This shows that large debt does not affect investors to keep investing in the company, only investors are interested in the allocation of corporate social responsibility funds issued by the company, so that corporate social responsibility funds can be profitable for investors.